Circular RNAs are associated with the resistance to Newcastle disease virus infection in duck cells - Fan, Lei; Ren, Jinlian; Wang, Yinchu; Chen, Yiyi; Chen, Yichun; Chen, Libin; Lin, Qiuyan; Liao, Ming; Ding, Chan; Xiang, Bin; Ren, Tao (Frontiers in Veterinary Science, 2023)
Newcastle disease virus (NDV) is prevalent worldwide with an extensive host range. Among birds infected with velogenic NDV strains, chickens experience high pathogenicity and mortality, whereas ducks mostly experience mild symptoms or are asymptomatic. Ducks have a unique, innate immune system hypothesized to induce antiviral responses. Circular RNAs (circRNAs) are among the most abundant and conserved eukaryotic transcripts. These participate in innate immunity and host antiviral response progression. circRNA expression profile differences post-NDV infection in duck embryo fibroblast (DEF) cells were analyzed using circRNA transcriptome sequencing. NDV infection altered circRNA expression profiles in DEF cells, and 57 significantly differentially expressed circRNAs were identified post-NDV infection. DEF responded to NDV by forming circRNAs to regulate apoptosis-, cell growth-, and protein degradation-related pathways via gene ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses. circRNA-miRNA-mRNA interaction networks demonstrated that DEF cells combat NDV infection by regulating cellular pathways or apoptosis through circRNA-targeted mRNAs and miRNAs. circ-FBXW7 overexpression and knockdown inhibited and promoted viral replication, respectively. DEF cells mainly regulated cell cycle alterations or altered cellular sensing to combat NDV infection. These results demonstrate that DEF cells exert antiviral responses by forming circRNAs, providing novel insights into waterfowl antiviral responses.